Occurrence of microplastics in gastrointestinal tracts and gills of fish from Beibu Gulf, South China Sea. (March 2020) - Koongolla, J. Bimali; Lin, Lang; Pan, Yun-Feng; Yang, Chang-Ping; Sun, Dian-Rong; Liu, Shan; Xu, Xiang-Rong; Maharana, Dusmant; Huang, Jian-Sheng; Li, Heng-Xiang
Abstract: Microplastics are widespread across the global oceans, yet the potential risks of the ubiquitous environmental contaminant to marine organisms has been less known. Accumulation of microplastics and associated contaminants in marine fish, may pose adverse impacts to human health via seafood consumption. This study evaluated microplastic contamination in 24 fish species collected from Beibu Gulf, one of the world's largest fishing grounds in South China Sea. Microplastics were detected in 12 fish species at an abundance of 0.027–1.000 items individual −1 and found in fish stomach, intestines and gills with the count percentage of 57.7%, 34.6% and 7.7%, respectively. Transparent fibers were observed as the predominant microplastics, which might be ingested accidently by fish or transferred through other animals at lower trophic levels. Majority of microplastics were identified as polyester (44%) and nylon (38%), whereas polypropylene (6%), polyethylene (6%), and acrylics (6%) were also found. Relatively, higher microplastic abundances were found in demersal fish compared to the pelagic species. Overall, the abundance of microplastics was documented as relatively low in the commercial fish collected from the open water of Beibu Gulf, South China Sea. Graphical abstract: Image 1 Highlights: Microplastics were present in 12 fish species from Beibu Gulf, South China Sea. Microplastic abundance ranged from 0.027 to 1.000 items individual −1 in different species. The polymer types were detected predominantly as polyester and nylon. Fibers were the dominant form and accounted for 96% of microplastics. Abstract : The main finding of the work: This study documented microplastics was considerably low in commercial fish collected from Beibu Gulf, South China Sea.